Trajectories of Kinematic Risky Driving Among Novice Teenagers - Simons-Morton, Bruce G. (2012)
OBJECTIVES: Elevated gravitational force event rates are associated with the likelihood of a crash or near crash and provide an objective measure of risky driving. The purpose of this research is to examine the patterns over time of kinematic measures of risky driving among novice teenage drivers. METHODS: Driving data were collected from 42 newly-licensed teenage drivers during the first 18 months of licensure. Data recording systems installed in participants’ vehicles provided information on driving performance and driver characteristics. Latent class and logistic regression models were used to analyze trajectories of elevated gravitational-force (g-force) event rates, called kinematic risky driving, with respect to risk groups and associated factors. RESULTS: Kinematic risky driving over the 18-month study period was best characterized as two classes, a higher-risk and a lower-risk class. The rate of kinematic risky driving during the first 6 months generally maintained over 18 months. Indeed, of those classified by latent class analysis as higher risk, 88.9%, 94.4% and 94.4% had average event rates above the median in the 1(st), 2(nd), and 3(rd) 6-month periods, respectively, indicating substantial tracking over time. Friends’ risky driving, friends’ risky behavior, self-reported risky driving, and perceptions about risky driving and driving privileges were associated with trip-level rates of kinematic risky driving. However, none of these factors was associated with trip-level rates after stratifying by overall risk in a latent class model, although friend’s risky driving was marginally significant. CONCLUSION: Kinematic risky driving tended to track over time within the lower and higher risky driving groups. Self-reported risky driving and having risky friends were predictors of kinematic risky driving rates, but these variables did not explain the heterogeneity within higher and lower classes of risky drivers.